2019
DOI: 10.1007/978-3-030-16667-0_5
|View full text |Cite
|
Sign up to set email alerts
|

Swarm-Based Identification of Animation Key Points from 2D-medialness Maps

Abstract: In this article we present the use of dispersive flies optimisation (DFO) for swarms of particles active on a medialness map-a 2D field representation of shape informed by perception studies. Optimising swarms activity permits to efficiently identify shape-based keypoints to automatically annotate movement and is capable of producing meaningful qualitative descriptions for animation applications. When taken together as a set, these keypoints represent the full body pose of a character in each processed frame. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
2
1

Relationship

5
0

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
(16 reference statements)
0
5
0
Order By: Relevance
“…It was shown that DFO is more efficient in 85% and more reliable in 90% of the 28 standard optimisation benchmarks used; furthermore, when there exists a statistically significant difference, DFO converges to better solutions in 71% of problem set. Furthermore, DFO has been applied to various problems, including but not limited to medical imaging [2], optimising machine learning algorithms [5,6], training deep neural networks for false alarm detection in intensive care units [29], computer vision and quantifying symmetrical complexities [4], identifying animation key points from medialness maps [8] and analysis of autopoiesis in computational creativity [3].…”
Section: Swarm and Evolutionary Methodsmentioning
confidence: 99%
“…It was shown that DFO is more efficient in 85% and more reliable in 90% of the 28 standard optimisation benchmarks used; furthermore, when there exists a statistically significant difference, DFO converges to better solutions in 71% of problem set. Furthermore, DFO has been applied to various problems, including but not limited to medical imaging [2], optimising machine learning algorithms [5,6], training deep neural networks for false alarm detection in intensive care units [29], computer vision and quantifying symmetrical complexities [4], identifying animation key points from medialness maps [8] and analysis of autopoiesis in computational creativity [3].…”
Section: Swarm and Evolutionary Methodsmentioning
confidence: 99%
“…It has been demonstrated that DFO has outperformed these algorithms and is used as the optimiser in this work. This algorithm belongs to the broad family of swarm intelligence and evolutionary computation techniques and has been applied to a diverse set of problems including: medical imaging [23], solving diophantine equations [24], PID speed control of DC motor [25], optimising machine learning algorithms [26,27], training deep neural networks for false alarm detection in intensive care units [28], computer vision and quantifying symmetrical complexities [29], identifying animation key points from medialness maps [30], and the analysis of autopoiesis in computational creativity [31].…”
Section: Population-based Optimisermentioning
confidence: 99%
“…ϕ is invariably set to 1 and ∆ to 0.001 in published studies (e.g. [3,6,31,7,5]). The upper bound on ϕ is derived from a convergence analysis for stochastic difference equations [11]).…”
Section: Swarm Optimisationmentioning
confidence: 99%